Barriers and enablers influencing female athlete return-to-sport postpartum: a scoping review - Tighe, B. J.; Williams, S. L.; Porter, C.; Hayman, M. (British Journal of Sports Medicine, 2023)
Objective Motherhood within sport has become more common with many female athletes seeking to return-to-sport (RTS) postpartum; yet few sport organisations possess policies that support female athletes to RTS postpartum. Our aim was to synthesise existing literature to identify the barriers and enablers that influence female athlete RTS postpartum to help guide the development of evidence-based policies to support postpartum athlete RTS.